An??lise de planos de gerenciamento de res??duos da constru????o civil em obras do munic??pio de S??o Paulo e regi??o - Bezerra, Claudia Maria da Silva (2019)
The construction industry has significant importance in the world economic scenario, considering its representativeness in the Gross Domestic Product (GDP) of several countries. However, the environmental impacts are also representative, mainly due to the excessive generation of waste from the construction and demolition activities. Faced with this reality, governments, through specific legislation, have taken steps to minimize these impacts. Among them is the obligation to elaborate and implement Civil Construction Waste Management Plans (PGRCC) and present them to the municipal authorities to obtain a construction permit. In this way, the objective of this research was to analyze seven PGRCCs of buildings located in the city of S??o Paulo and region, as well as to verify which management and management practices are being reported. To this end, indicators based on relevant legislation and environmental and quality management systems have been developed. The indicators were submitted to a group of specialists composed of professionals in the area of construction waste management, in order to establish a ranking of importance and distribution of weights among them. The methodology of this research, by its characteristics, fits as documentary research, as to nature, it is an applied research, with a qualitative approach and with regard to the objectives, it can be defined as exploratory. The PGRCC were classified with the purpose of verifying the degree of adherence to the environmental practices presented in the bibliography used. A comparison was then made between the PGRCCs to identify trends and distinctions between them. It was identified that the PGRCCs meet the minimum requirements established by CONAMA Resolution 307 (2002); however, some practices were not met, which would greatly improve the effectiveness of RCC management. It was verified that the practices that stood out the most were: planning, transportation, reuse and recycling in the work itself. The PGRCCs prepared by advisory companies presented better grades, but it is observed that these are elaborated in an identical way, not taking into account the specificities of each work.